Nilai Perusahaan Dipengaruhi Oleh Tax Avoidance Dan Profitabilitas - Annesa Adriyani; Aswad, Hijratul (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
This research aims to examine the effect of tax avoidance and profitability on company value (in property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period). The research method used is a quantitative research method. The sample in this research was 21 property and real estate sub-sector companies that went public. The data collection method used in this research is the documentation method from secondary data. The data analysis method used in this research is multiple linear regression analysis with the help of the SPSS (Statistical Product and Service Solution) program. Based on the research results, it shows that tax avoidance and profitability influence company value